2004
DOI: 10.1897/03-221
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic transformation of compounds of technical toxaphene. 2. Fate of compounds lacking geminal chlorine atoms

Abstract: The major toxaphene metabolites in sediment and soils (2-exo,3-endo,6-exo,8,9,10-hexachlorobornane [B6-923] and 2-endo,3-exo,5-endo,6-exo,8,9,10-heptachlorobornane [B7-1001]) were incubated with the isolated gram-negative bacterium Dehalospirillum multivorans. Within 14 d, biotransformation of B7-1001 was nearly quantitative, resulting in two penta- and six hexachlorobornanes, as well as one unsaturated hexachloro compound of technical toxaphene. The major transformation product (approximately 50% of all metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 39 publications
2
25
0
7
Order By: Relevance
“…Based on GC×GC retention times and mass spectra, we confirmed that the toxaphene congeners found in the samples matched those from the toxaphene technical product. By comparing our data with the relative retention times and characteristic mass spectra in the literature (15,16), we were able to verify that they were the most abundant toxaphene congeners found in the environment (B8-1413, B8-1414/B8-1945, B8-2229, B9-1679, and B9-1025). R-Chlordene and 1-chloro-2,2-bis(chlorophenyl)ethene (p,p'-DDMU) which is the dechlorinated form of 1,1-dichloro-2,2-bis(chlorophenyl)ethane (p,p'-DDE) were also identified using the library database.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Based on GC×GC retention times and mass spectra, we confirmed that the toxaphene congeners found in the samples matched those from the toxaphene technical product. By comparing our data with the relative retention times and characteristic mass spectra in the literature (15,16), we were able to verify that they were the most abundant toxaphene congeners found in the environment (B8-1413, B8-1414/B8-1945, B8-2229, B9-1679, and B9-1025). R-Chlordene and 1-chloro-2,2-bis(chlorophenyl)ethene (p,p'-DDMU) which is the dechlorinated form of 1,1-dichloro-2,2-bis(chlorophenyl)ethane (p,p'-DDE) were also identified using the library database.…”
Section: Resultsmentioning
confidence: 73%
“…Several halogenated natural products (HNPs) were detected in the extracts: halogenated 1′-methyl-1,2′-bipyrroles (MBPs), DMBPs, meth- 41)). d Identified by the correct retention time range on the DB-5 column type, the correct number of chlorines, characteristic features in the mass spectra, and their known abundance in cod liver oil (15,16). e Structure tentatively assigned based on the presence of these toxaphenes in cod liver oil and the known elution order on the DB-5 column type (15,16) f Tentative structural identification: 2,2′,3,3′-tetrabromo-4,4′5,5′-tetrahydroxy diphenyl methane.…”
Section: Resultsmentioning
confidence: 99%
“…Toxaphene weathers in different ways in different environmental settings to produce different congener mixtures (Ruppe et al, 2003(Ruppe et al, , 2004. In addition, different animals metabolize various toxaphene congeners to varying degrees (Angerhofer et al, 1999) and different species of animals end up with different toxaphene congener profiles comprising their respective body burdens.…”
Section: Weathering Of Toxaphenementioning
confidence: 99%
“…The persistence of the various congeners is determined by their thermodynamic stabilities and molecular structural energies (Heimstad et al, 2001). Microbial degradation of toxaphene shows specificity for the removal of chlorines in particular positions on the molecule (Ruppe et al, 2003(Ruppe et al, , 2004. In addition, biotic and abiotic transformation of toxaphene results in different mixtures of congeners (Angerhofer et al, 1999).…”
Section: Is the Cle Representative Of Wt?mentioning
confidence: 99%
“…For instance, the anaerobic gram negative bacterium Sulfurospirillum multivorans [5] (previously known as Dehalospirillum multivorans [6]) showed a high potential for the anaerobic transformation of tetrachloroethene (PCE) and related C 2 -compounds [7,8]. Our lab studies demonstrated that S. multivorans was also an excellent transformer of the chloropesticide toxaphene [9,10]. Toxaphene is formed by the exhaustive chlorination of camphene which yields a complex mixture of about 1000 penta-to decachlorinated compounds of technical toxaphene (CTTs) [11,13].…”
Section: Introductionmentioning
confidence: 99%